Hepatitis C virus infection triggers a tumor‐like glutamine metabolism. Issue 3 (3rd February 2017) - Lévy, Pierre L.; Duponchel, Sarah; Eischeid, Hannah; Molle, Jennifer; Michelet, Maud; Diserens, Gaëlle; Vermathen, Martina; Vermathen, Peter; Dufour, Jean‐Francois; Dienes, Hans‐Peter; Steffen, Hans‐Michael; Odenthal, Margarete; et al.
Abstract : Chronic infection with hepatitis C virus (HCV) is one of the main causes of hepatocellular carcinoma. However, the molecular mechanisms linking the infection to cancer development remain poorly understood. Here we used HCV‐infected cells and liver biopsies to study how HCV modulates the glutaminolysis pathway, which is known to play an important role in cellular energetics, stress defense, and neoplastic transformation. Transcript levels of glutaminolytic factors were quantified in Huh7.5 cells or primary human hepatocytes infected with the Japanese fulminant hepatitis 1 HCV strain as well as in biopsies of chronic HCV patients. Nutrient deprivation, biochemical analysis, and metabolite quantification were performed with HCV–infected Huh7.5 cells. Furthermore, short hairpin RNA vectors and small molecule inhibitors were used to investigate the dependence of HCV replication on metabolic changes. We show that HCV modulates the transcript levels of key enzymes of glutamine metabolism in vitro and in liver biopsies of chronic HCV patients. Consistently, HCV infection increases glutamine use and dependence. We finally show that inhibiting glutamine metabolism attenuates HCV infection and the oxidative stress associated with HCV infection. Conclusion : Our data suggest that HCV establishes glutamine dependence, which is required for viral replication, and, importantly, that glutamine addiction is a hallmark of tumor cells. While HCV induces glutaminolysis to create an environment favorable for viral replication, it predisposes the cell to transformation. Glutaminolytic enzymes may be interesting therapeutic targets for prevention of hepatocarcinogenesis in chronic hepatitis C. (Hepatology 2017;65:789‐803).